Price, perceived value, customer satisfaction and favourable repeat purchase intention of malaysian low cost airlines - Yeoh, Ei Leen (2013)
Before the emergence of the low cost airlines, air travel is a luxury that only the corporate, business and upper-middle income segments could afford. The most significant change brought by the Malaysian low cost airlines is the creation of new market segments. The Malaysian low cost airlines have converted the previously non user groups including segments of individuals who could not afford air travel before into existing customers. Hence, the existing domestic customers of the Malaysian low cost airlines are presumed to be different from the leisure air travellers on full service airlines. The research objective of this study is to explain low price, perceived value, satisfaction and favourable repeat purchase intention of the Malaysian low cost airlines resulting from the existing domestic customers' experiences. Qualitative research approach was chosen as the research methodology. This study employed purposive sampling in order to obtain rich information cases. Data were collected from 22 semi-structured interview sessions and 11 complete observer observations. This research has found that lower airfare means low level of service and a mode of transport. An notable finding is that the airfare means "value-for-money", only if the amount paid is either zero or extremely low during the airlines' price promotional period. Findings indicated that the existing domestic customers of Malaysian low cost airlines weighed perceived benefits against perceived costs of travelling on low cost airlines simultaneously they also perceived functional value, relative value and social value. Interestingly, findings revealed that customer satisfaction is low expectation towards service performance and dissatisfaction is non durable. This research also found that favourable repeat purchase intention of air travel on the low cost airlines are due to several key influential factors including price, price and flight destination, price and perceived value, satisfaction, price and satisfaction, and price, perceived value and satisfaction.